Daytime and nighttime sleep patterns in adolescents with and without chronic pain - Law, Emily F. (2011)
OBJECTIVE: The aims of the current study were to characterize daytime and nighttime sleep patterns of adolescents with chronic pain, and to compare their sleep patterns to a healthy age and sex-matched cohort. METHODS: Sixty-one adolescents from a pain clinic and 60 age and sex-matched youth from the community (mean age = 15.07; 69% female) participated. Participants underwent 10 days of actigraphic sleep monitoring to assess total sleep time (minutes of estimated sleep at night), wake minutes after initial sleep onset, sleep efficiency, and occurrence of sleep during the day. RESULTS: Adolescents with chronic pain and healthy youth had similar nighttime sleep patterns (total sleep time, wake minutes after initial sleep onset, and sleep efficiency). However, adolescents with chronic pain spent more time sleeping during the day than their healthy peers. Longer daytime sleep was associated with more activity limitations in youth with chronic pain. CONCLUSION: Although previous research using self-report methodology has indicated that adolescents with chronic pain commonly endorse poor sleep, findings from the current study suggest that these complaints may not be explained by differences in nighttime sleep patterns as measured by actigraphy. Use of multidimensional sleep assessment may help to understand the potential impact of sleep on chronic pain in adolescents.